Model Laboratorium Gerusan Lokal Pada Pilar Jembatan Tipe Grouped Cylinder - Arie Perdana Putra; Mudjiatko Mudjiatko; Siswanto Siswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Local scour at bridge pillars that occurs continuously will cause damage to the bridge structure. Many forms of pillar have been developed to minimize local scouring, but yet provide maximum results. Laboratory model has been developed to identify the local scour phenomena on the grouped cylinder pillar by looking at the phenomena with and without pillar protector. The bed of model is using Kampar sand with grain size d35 = 0,285 mm, d50 = 0,330 mm and d65 = 0,380 mm and Gs = 2,63. Three variations of the flow used in this research is classified on the type of subcritical flow with Froude number ranged from 0,46354 – 0,76903. Reynolds number in Fr1 scored 1658,416 then included in the transitional flow and turbulent flow occur in Fr2 scored 3081,683 and Fr3 scored 4381,188. Hjulstorm graphic shows that the granules of gradation used in this research in moving zone. Hydrodynamic flow in pillar causes downflow on the front pillar and wake vortices are formed on the back, so that the presence of these forces will create a horseshoe vortex at the bottom of the pillar. The equilibrium of scour depth against time function occurred at minute 75. The maximum ratio of scour depth (ds/b)  is 2,9 which occurs in Q3P. Pillar protector of curtain type can reduce scour depths  of up to 62,07 %. Sediment transport analysis result prove that the higher Froude number is used the bigger the granules are transported.  Key word  : local scouring, laboratory model, grouped cylinder pillar, hydrodynamic flow, depth ratio.